1.
![\left\{{{x+y=5}\atop{x-y^2=3}}\right. \left\{{{x+y=5}\atop{x-y^2=3}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7Bx%2By%3D5%7D%5Catop%7Bx-y%5E2%3D3%7D%7D%5Cright.)
![\left\{{{x+y=5}\atop{x-y^2=3|*(-1)}}\right.\\\\\left\{{{x+y=5}\atop{-x+y^2=-3}}\right. \left\{{{x+y=5}\atop{x-y^2=3|*(-1)}}\right.\\\\\left\{{{x+y=5}\atop{-x+y^2=-3}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7Bx%2By%3D5%7D%5Catop%7Bx-y%5E2%3D3%7C%2A%28-1%29%7D%7D%5Cright.%5C%5C%5C%5C%5Cleft%5C%7B%7B%7Bx%2By%3D5%7D%5Catop%7B-x%2By%5E2%3D-3%7D%7D%5Cright.)
сложим эти уравнения:
![x+y-x+y^2=5-3 x+y-x+y^2=5-3](https://tex.z-dn.net/?f=x%2By-x%2By%5E2%3D5-3)
x_1=5-(-2)=7\\\\y_2=1;=>x_2=5-1=4" alt="y^2+y-2=0\\\\D=1-4*1*(-2)1+8=9=3^2\\\\y_1=\frac{-1-3}{2}=-2\\\\y_1=-2\\\\y_2=\frac{-1+3}{2}=1\\\\\\y_2=1\\\\y_1=-2;=>x_1=5-(-2)=7\\\\y_2=1;=>x_2=5-1=4" align="absmiddle" class="latex-formula">
Ответ: (7; -2); (4; 1)
2.
![\sqrt{-x^2+7x-10} \sqrt{-x^2+7x-10}](https://tex.z-dn.net/?f=%5Csqrt%7B-x%5E2%2B7x-10%7D)
ОДЗ:
![-x^2+7x-10\geq0\\\\x^2-7x+10\leq0\\\\(x-2)*(x-5)\leq0 -x^2+7x-10\geq0\\\\x^2-7x+10\leq0\\\\(x-2)*(x-5)\leq0](https://tex.z-dn.net/?f=-x%5E2%2B7x-10%5Cgeq0%5C%5C%5C%5Cx%5E2-7x%2B10%5Cleq0%5C%5C%5C%5C%28x-2%29%2A%28x-5%29%5Cleq0)
+ - +
______________|________________|_______________________
2 5
2 ≤ x ≤ 5
x ∈ [2; 5]